The Structure, Composition, and Role of Periplasmic Stator Scaffolds in Polar Bacterial Flagellar Motors - Zhou, Xiaotian; Roujeinikova, Anna (Frontiers in Microbiology, 2021)
In the bacterial flagellar motor, the cell-wall-anchored stator uses an electrochemical gradient across the cytoplasmic membrane to generate a turning force that is applied to the rotor connected to the flagellar filament. Existing theoretical concepts for the stator function are based on the assumption that it anchors around the rotor perimeter by binding to peptidoglycan. The existence of another anchoring region on the motor itself has been speculated upon, but is yet to be supported by binding studies. Due to the recent advances in electron cryotomography, evidence has emerged that polar flagellar motors contain substantial proteinaceous periplasmic structures next to the stator, without which the stator does not assemble and the motor does not function. These structures have a morphology of disks, as is the case with Vibrio spp., or a round cage, as is the case with Helicobacter pylori. It is now recognized that such additional periplasmic components are a common feature of polar flagellar motors, which sustain higher torque and greater swimming speeds compared to peritrichous bacteria such as Escherichia coli and Salmonella enterica. This review summarizes the data available on the structure, composition and role of the periplasmic scaffold in polar bacterial flagellar motors and discusses the new paradigm for how such motors assemble and function.